Money secrets: How does trade secret legal protection affect firm market value? Evidence from the uniform trade secret act. (19th July 2016) - Castellaneta, Francesco; Conti, Raffaele; Kacperczyk, Aleksandra
Abstract : Research summary : We investigate the impact of trade secret legal protection on firm market value in the context of acquisitions. On one hand, market value may increase because trade secret assets become better protected from rivals. On the other hand, market value may decrease because trade secret protection reduces information about the target and its competitors available to potential buyers, increasing uncertainty about its value. Buyers will discount their offers in expectation of being compensated for riskier deals. Using a sample of private equity investments in the United States, we find that trade secret protection has a positive effect in industries with high mobility of knowledge workers, but a negative effect in industries with (1) high resource–value uncertainty and (2) high poor‐investment risk. Managerial summary : We argue that an increase in trade secret legal protection might not unequivocally benefit firm owners when selling their business. A stronger trade secret protection increases the market value of firms in industries with high workers' mobility, but it decreases the market value of firms in industries with uncertain resource value and/or high risk of poor‐acquisition investments. Based on the contingent effect of trade secret protection, companies may want to adjust their strategic decisions, including where to locate or relocate, based in part on whether they will derive benefits or suffer losses when trade secrets are better protected. Finally, our study should help policymakers understand more fully the economic impact of government policies associated with trade secrets. Copyright © 2016 John Wiley & Sons, Ltd.